Analysis of factors influencing adoption of dairy technologies in western Kenya - Makokha, S.N.; Karugia, Joseph T.; Staal, Steven J.; Oluoch-Kosura,Willis (African Association of Agricultural Economists, 2008)
Indicators of poverty in western Kenya show high poverty levels. The area has low dairy development yet the potential for dairy development is quite high. Dairy farming has the potential to reduce poverty by increasing incomes and reducing unemployment. This paper reports factor interrelationships in dairy adoption with a view to understanding factors that influence adoption. The binary probit model was used to analyse data from 1575 households. Contrary to findings from similar studies elsewhere, some factors had a negative association with adoption, thus unfolding a unique adoption process. The association between the factor interactive affects and technology adoption highlighted the importance of exploring factor interrelationships. The widely held conclusion that smallholder households are resource constrained in technology adoption did not hold in this study. The source of labour supply dictated choice of variables to be used as proxies for labour availability. The exploration of endogenous relationships in the various factors dictated the use of the single probit model. The spatial factors used were highly significant in adoption, and the predicted probabilities from these factors gave a true spatial prediction. This confirmed reliability of the probit estimates. An understanding of factor interrelationships in adoption gives adoption studies high specificity while making conclusions and recommendations, thus necessitating case studies in adoption.